Quality of Differently Dried Osmanthus fragrans Pomace: Physical Properties, Nutrient Composition, Antioxidant and Tyrosinase Inhibitory Activity - GUO Yingjie, BIAN Jianming, XIE Qiutao, LI Gaoyang, WANG Kai, ZHU Xiangrong (Shipin Kexue, 2025)
The aim of this study was to investigate and evaluate the processing adaptability of Osmanthus fragrans pomace, a by-product of O. fragrans extract, in order to provide a reference for its rational utilization. We examined the physical properties, nutrient composition, antioxidant capacity and tyrosinase inhibitory activity of O. fragrans pomace prepared by vacuum microwave drying (VMD), vacuum freeze drying (VFD), or heat pump drying (HPD). The results showed that the VFD sample had good color with the lowest ΔE and browning index of 14.26 ± 0.53 and 12.43 ± 0.65, respectively, and possessed the highest contents of total phenols and total flavonoids, and exhibited the highest water-holding capacity and antioxidant capacity. The VMD sample possessed the highest contents of soluble dietary fiber, total phenylethanol glycosides, actecoside, and salidroside, and exhibited the strongest oil-holding capacity and tyrosinase inhibitory activity. Pearson correlation analysis showed that the antioxidant capacity was significantly and positively correlated with the contents of total phenols and total flavonoids, and the tyrosinase inhibitory activity was significantly and positively correlated with the contents of total phenylethanol glycosides, total sugars, and total tannins. Partial least squares-discriminant analysis (PLS-DA) could distinguish differently dried O. fragrans pomace and the proposed model was stable with good predictability. According to Topsis analysis, the VFD sample had the best quality, and the VMD sample was superior to the HPD sample. In conclusion, O. fragrans pomace has good physical properties, nutrient composition, antioxidant capacity, and tyrosinase inhibitory activity, thereby holding potential as a raw material for functional food and whitening cosmetics. This study provides a reference for the application of differently dried O. fragrans pomace.